Surface reconstruction of wide-bandgap perovskites enables efficient perovskite/silicon tandem solar cells - Zheng Fang; Bingru Deng; Yongbin Jin; Liu Yang; Lisha Chen; Yawen Zhong; Huiping Feng; Yue Yin; Kaikai Liu; Yingji Li; Jinyan Zhang; Jiarong Huang; et al. (Nature Communications)
Abstract Wide-bandgap perovskite solar cells (WBG-PSCs) are critical for developing perovskite/silicon tandem solar cells. The defect-rich surface of WBG-PSCs will lead to severe interfacial carrier loss and phase segregation, deteriorating the device’s performance. Herein, we develop a surface reconstruction method by removing the defect-rich crystal surface by nano-polishing and then passivating the newly exposed high-crystallinity surface. This method can refresh the perovskite/electron-transporter interface and release the residual lattice strain, improving the charge collection and inhibiting the ion migration of WBG perovskites. As a result, we can achieve certified efficiencies of 23.67% and 21.70% for opaque and semi-transparent PSCs via a 1.67-eV perovskite absorber. Moreover, we achieve four-terminal perovskite/silicon tandem solar cells with a certified efficiency of 33.10% on an aperture area of one square centimeter.